MECHANICAL AND MAGNETIC PROPERTIES OF BONDED MAGNET Nd2Fe14B PRODUCED USING BINDER BAKELITE - Muljadi, -; Sardjono, Priyo; Sebayang, Perdamean (Teknologi Indonesia, 2014)
Bonded magnet Nd2Fe14B was made with mixing Nd2Fe14B powder and polymer bakelite using compressing method. The bakelite concentration was varied of 5 wt%, 10 wt%, 15 wt%, and 20 wt%. Both Nd2Fe14B and bakelite powders were mixed and milled for 24 hours using a ball mill. The powder was formed by dry pressing and subsequently dried in a drying cabinet at a temperature of 180oC for 4 hours. Then, magnetization process was done using impulse magnetizer, and performed measurements of the magnetic properties such as flux density, remanenceBr, coercivity Hic and energy density (BH)max using Gaussmeter and hysteresis permeagraph. Characterization of mechanical properties such as bending strength (BS) and vickers hardness (Hv) was determined before magnetization. Bakelite concentration had a significant influence on both magnetic and mechanical properties. From the characterization results, the optimum concentration of bakelite was 10% and 15% wt. Bonded Nd2Fe14B magnet obtained had the following properties: BS value of 27.7433.42 MPa, Hv value of 292.65314.33 MPa, the value of the magnetic flux density from 1360 to 1400 Gauss, remanence Br = 4.995:02 kG, coercivity Hic = 7.8 kOe, and energy density (BH)max about 5.13 to 5.24 MGOe at the optimum concentration.